Sugarcane photosynthesis and associated leaf traits in response to high [CO2] and drought - Cardenal Rubio, Zulma Catherine (2022)
Expected changes in climate, such as increased atmospheric CO2 concentration and variation in rainfall, will affect the photosynthetic metabolism of plants and, therefore, crop productivity. The increase in CO2 can benefit plants as it increases photosynthetic rate and water use efficiency by reducing stomatal conductance. In this regard, it is widely accepted in the scientific community that the positive effects of CO2-enriched atmospheres are more marked in plants with C3 metabolism as a consequence of the inefficiency in the photosynthetic process, associated with the desaturation of the Rubisco enzyme in the current CO2 levels and with photorespiration. Thus, the elevated concentration of CO2 [CO2] improves the efficiency of the photosynthetic process by limiting photorespiration and increasing the concentration of CO2 near the Rubisco active site. On the other hand, C4 plants theoretically do not respond to the increase in [CO2], since they already have a concentration mechanism in the vascular bundle sheath cells. However, it has been reported that sugarcane plants (C4) show increases in photosynthesis, changes in growth and increases in biomass. Therefore, it was suggested that the C4 metabolism in these plants does not show maximum efficiency under the current CO2 condition and that the limitation in the expression of the maximum efficiency of the photosynthetic process may be caused by failures, either in the carboxylation or decarboxylation phase.Thus, the aim was to identify the key processes of C4 metabolism involved with the limitation in the mechanism of CO2 concentration in sugarcane. The study was conducted in open-top chambers using two sugarcane varieties (RB867515 and RB855536). These were grown under two CO2 environments (400 and 680 μmol CO2 mol-1 of air) and exposed to water restriction in order to potentiate failures in metabolism. Biometric, anatomical, biomass partitioning and A/Ci and A/Q curves under 21% and 2% O2 were analyzed. Overview, it was found that the variety most responsive to high CO2 was RB855536, and it was concluded that in the current CO2 condition the photosynthetic process of sugarcane plants may be limited by the elevated carboxylation rate of PEPC in relation to Rubisco which leads to leakage of CO2 from the bundle sheath cells to the mesophyll cells, resulting in lower quantum carboxylation efficiency. At the same time, we indicate that plants are able to modulate their metabolism in favor of water conservation at the leaf level, since in this study, they superimposed the efficient use of water over the gain in C by eCO2, which is a typical acclimation response under atmospheres enriched with this gas.